2021
DOI: 10.1111/1462-2920.15531
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and proteomic profiles of biofilms on microplastics are decoupled from artificial surface properties

Abstract: Microplastics in marine ecosystems are colonized by diverse prokaryotic and eukaryotic communities. How these communities and their functional profiles are shaped by the artificial surfaces remains broadly unknown. In order to close this knowledge gap, we set up an in situ experiment with pellets of the polyolefin polymer polyethylene (PE), the aromatic hydrocarbon polymer polystyrene (PS), and wooden beads along a coastal to estuarine gradient in the Baltic Sea, Germany. We used an integrated metagenomics/ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 83 publications
4
64
2
Order By: Relevance
“…Previous research from marine environments showed similar results to those observed in this study, reporting that geography is likely to be a stronger predictor of plastisphere community composition at the scale of ocean basins (Harrison et al, 2018 ; Oberbeckmann et al, 2021 ). However, this is still under debate with several studies suggesting substrate‐driven selection, with differences reported not only when comparing inert control material to plastic substrates (e.g., Miao et al, 2019 ; Ogonowski et al, 2018 ) but also when colonization on different plastic polymers was evaluated (e.g., Li et al, 2019 ; Pinto et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Previous research from marine environments showed similar results to those observed in this study, reporting that geography is likely to be a stronger predictor of plastisphere community composition at the scale of ocean basins (Harrison et al, 2018 ; Oberbeckmann et al, 2021 ). However, this is still under debate with several studies suggesting substrate‐driven selection, with differences reported not only when comparing inert control material to plastic substrates (e.g., Miao et al, 2019 ; Ogonowski et al, 2018 ) but also when colonization on different plastic polymers was evaluated (e.g., Li et al, 2019 ; Pinto et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Omitting the need for PCR and its associated biases, future investigations into the metagenomes or metatranscriptomes of these microbes and communities may reveal additional taxonomic details. Using genomics and proteomic profiling, Oberbeckmann et al (2021) reported that the properties of polyethylene and polystyrene pellets had little influence on their associated microbial communities, they were similar on both substrate types. Future community-based assessments, including from metagenomics and proteomics data, as used by Oberbeckmann et al (2021), may further help to identify appropriate sites for the later enrichment and isolation of potential plastic biodegrading organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using genomics and proteomic profiling, Oberbeckmann et al (2021) reported that the properties of polyethylene and polystyrene pellets had little influence on their associated microbial communities, they were similar on both substrate types. Future community-based assessments, including from metagenomics and proteomics data, as used by Oberbeckmann et al (2021), may further help to identify appropriate sites for the later enrichment and isolation of potential plastic biodegrading organisms. In particular, confirmation of the presence of complete plastic biodegradation pathways, along with their corresponding regulatory mechanisms could help to identify environments and sites for the mining of novel plastic degrading genes and taxa.…”
Section: Discussionmentioning
confidence: 99%
“…As positive controls, we tracked Kraft paper film and cotton fabric, both cellulosic in nature. As negative controls, we tracked a polyethylene (LDPE) film and polyethylene terephthalate (PETE) fabric. Time-lapse photography and mass loss measurements documented the disintegration of these materials.…”
Section: Introductionmentioning
confidence: 99%